Associations between work-related variables and workplace violence among Chinese medical staff: A comparison between physical and verbal violence - Sun, Long; Zhang, Wen; Cao, Aihua (Frontiers in Public Health, 2023)
Background Workplace violence (WPV) against medical staff has been an important public health and societal problem worldwide. Although numerous studies have implied the differences between physical violence (PV) and verbal violence (VV) against medical staff, few studies were conducted to analyze the different associations between work-related variables, PV, and VV, especially in China. Methods A cross-sectional study was conducted among Chinese medical staff in public hospitals, and 3,426 medical staff were interviewed and analyzed. WPV, including PV and VV, were evaluated by the self-report of the medical staff. Work-related variables, physical disease, depression, and social-demographic variables were also measured. The work-related variables included types of medical staff, professional titles, hospital levels, managers, working years, job changing, working hours/week, night duty times/week, monthly income, self-reported working environment, and social position. Logistic regressions were conducted to examine the factors associated with PV and VV. Results A total of 489 medical staff (23.0%) reported the experience of PV and 1,744 (50.9%) reported the experience of VV. Several work-related variables were associated with PV and VV, including nurse (OR = 0.56 for PV, p < 0.01; OR = 0.76 for VV, p < 0.05), manager (OR = 1.86 for PV, p < 0.01; OR = 1.56 for VV, p < 0.001), night duty frequency/week (OR = 1.06 for PV, p < 0.01; OR = 1.03 for VV, p < 0.01), bad working environment (OR = 2.73 for PV, p < 0.001; OR = 3.52 for VV, p < 0.001), averaged working environment (OR = 1.51 for PV, p < 0.05; OR = 1.55 for VV, p < 0.001), and bad social position (OR = 4.21 for PV, p < 0.001; OR = 3.32 for VV, p < 0.001). Working years (OR = 1.02, p < 0.05), job changing (OR = 1.33, p < 0.05), and L2 income level (OR = 1.33, p < 0.01) were positively associated with VV, but the associations were not supported for PV (all p>0.05). The other associated factors were male gender (OR = 1.97 for PV, p < 0.001; OR = 1.28 for VV, p < 0.05) and depression (OR = 1.05 for PV, p < 0.001; OR = 1.04 for VV, p < 0.001). Conclusion Both PV and VV were positively associated with work-related variables, such as doctor, manager, more night duty frequency, perceived bad working environment, or social position. Some variables were only associated with VV, such as working years, job changing, and monthly income. Some special strategies for the work-related variables should be applied for controlling PV and VV.